TeV gamma rays expected from supernova remnants in different uniform interstellar media - Berezhko, Evgeny; Völk, Heinrich J. (Astroparticle physics, 2000)
Calculations of the expected TeV γ-ray emission, produced by accelerated cosmic rays (CRs) in nuclear collisions, from supernova remnants evolving in a uniform interstellar medium (ISM) are presented. The aim is to study the sensitivity of γ-ray production to a physical parameter set. Apart from its general proportionality to NH, it is shown that the γ-ray production essentially depends upon the ratio of the CR diffusion coefficient κ to a critical value κcrit=10(B0/5μG)(NH/0.3cm−3)−1/3κB, where B0 and NH are the magnetic field and hydrogen number density of the ISM, and κB denotes the Bohm diffusion coefficient. If κ is of the same order or lower than κcrit, then the peak TeV γ-ray flux in the Sedov evolutionary phase, normalized to a distance of 1 kpc, is about 10−10(NH/0.3cm−3) photons cm−2s−1. For a CR diffusion coefficient that is significantly larger than κcrit, the CR cutoff energy is less than 10 TeV, and the expected γ-ray flux at 1 TeV is considerably below the presently detectable level of 10−12 photons cm−2s−1. The same is of course true for a supernova remnant in the rarified, so-called hot ISM.
Gesehen am 08.12.2020